Profiling Microglia From Alzheimer’s Disease Donors and Non-demented Elderly in Acute Human Postmortem Cortical Tissue - Alsema, Astrid M.; Jiang, Qiong; Kracht, Laura; Gerrits, Emma; Dubbelaar, Marissa L.; Miedema, Anneke; Brouwer, Nieske; Hol, Elly M.; Middeldorp, Jinte; van Dijk, Roland; Woodbury, Maya; Wachter, Astrid; et al. (Frontiers in Molecular Neuroscience, 2020)
Microglia are the tissue-resident macrophages of the central nervous system (CNS). Recent studies based on bulk and single-cell RNA sequencing in mice indicate high relevance of microglia with respect to risk genes and neuro-inflammation in Alzheimer’s disease (AD). Here, we investigated microglia transcriptomes at bulk and single-cell level in non-demented elderly and AD donors using acute human post-mortem cortical brain samples. We identified 7 human microglial subpopulations with heterogeneity in gene expression. Notably, gene expression profiles and subcluster composition of microglia did not differ between AD donors and non-demented elderly in bulk RNA sequencing nor in single-cell sequencing.